Palmelloid formation in the Antarctic psychrophile, Chlamydomonas priscuii, is photoprotective - Szyszka-Mroz, Beth; Ivanov, Alexander G.; Trick, Charles G.; Hüner, Norman P. A. (Frontiers in Plant Science, 2022)
Cultures of the obligate, Antarctic psychrophile, Chlamydomonas priscuii grown at permissive low temperature (8°C) are composed of flagellated, single cells, as well as non-motile, multicellular palmelloids. The relative proportions of the two cell types are temperature dependent. However, the temperature dependence for palmelloid formation is not restricted to psychrophilic C. priscuii but appears to be a general response of mesophilic Chlamydomonas species (C. reinhardtii and C. raudensis) to non-permissive growth temperatures. To examine potential differences in photosynthetic performance between single cells versus palmelloids of the psychrophile, a cell filtration technique was developed to separate single cells from palmelloids of C. priscuii grown at 8°C. Flow cytometry was used to estimate the diameter of isolated single cells (≤ 5 μm) versus isolated palmelloids of varying size (≥ 8 μm). Compared to single cells, palmelloids of C. priscuii showed a decrease in the abundance of light harvesting complex II (LHCII) proteins with a 2-fold higher Chl a/b ratio. A decrease in both lutein and β-carotene in palmelloids resulted in carotenoid pools which were 27% lower in palmelloids compared to single cells of the psychrophile. Chlorophyll fluorescence analyses of the isolated fractions revealed that maximum photochemical efficiency of PSII (Fv/Fm) was comparable for both single cells and palmelloids of C. priscuii. However, isolated palmelloids exhibited lower excitation pressure, measured as 1 - qL, but higher yield of PSII (ΦPSII) and 50% higher rates of electron transport (ETR) than single cells exposed to high light at 8°C. This decreased sensitivity to high light in isolated palmelloids compared to single cells was associated with greater non-regulated dissipation of excess absorbed energy (ΦNO) with minimal differences in ΦNPQ in C. priscuii in response to increasing irradiance at low temperature. The ratio ΦNO/ΦNPQ observed for isolated palmelloids of C. priscuii developed at 8°C (1.414 ± 0.036) was 1.38-fold higher than ΦNO/ΦNPQ of isolated single cells (1.021 ± 0.018) exposed to low temperature combined with high light (1000 µmol m-2 s-1). The differences in the energy quenching capacities between palmelloids and single cells are discussed in terms of enhanced photoprotection of C. priscuii palmelloids against low temperature photoinhibition.